2010
DOI: 10.1111/j.1365-2885.2009.01120.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, metabolism, and excretion of toceranib phosphate (Palladia™, SU11654), a novel tyrosine kinase inhibitor, in dogs

Abstract: Toceranib phosphate (Palladia, SU11654), a multireceptor tyrosine kinase inhibitor with anti-tumor and anti-angiogenic activity, has been developed for the treatment of mast cell tumors in dogs. An overview of the distribution, metabolism, and excretion of toceranib phosphate in dogs is presented. When [(14)C]-toceranib was orally administered to dogs, the majority of the radioactivity (92%) was excreted in feces and only a small portion (7%) was excreted in urine. Seven days after a single 3.25 mg/kg oral dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…In prior studies the Cmax was determined to be approximately 6–8 hours post drug administration [7,8]. Additionally, a pharmacodynamic study in dogs demonstrated that plasma concentrations of toceranib 8 hours post drug administration ranging from 30 to 180 ng/ml were associated with target modulation in vivo [5].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In prior studies the Cmax was determined to be approximately 6–8 hours post drug administration [7,8]. Additionally, a pharmacodynamic study in dogs demonstrated that plasma concentrations of toceranib 8 hours post drug administration ranging from 30 to 180 ng/ml were associated with target modulation in vivo [5].…”
Section: Resultsmentioning
confidence: 99%
“…Physical examination, routine bloodwork (CBC, biochemistry profile) and blood sampling for assessment of toceranib and VEGF plasma concentrations was performed pretreatment and on days 0, 7, 14 and 30 of treatment. On days 0, 7, and 14, blood was collected at 6 and 8 hours post drug administration to coincide with the predicted toceranib Cmax based on previous studies that had established the time of maximum drug concentration (Tmax) to be 5.3-9.3 hours [7,8]. On day 30, blood sampling was performed at 0, 1, 2, 6, 8, and 12 hours post drug administration to confirm either 6 or 8 hours as the true Cmax.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These compounds inhibit cancer cell proliferation and tumor growth via interaction with a variety of intracellular targets such as DNA, telomerase, tubulin, P glycoprotein, protein kinases and phosphatases [14]. Isatin-based hydrazones have been identified as inhibitors of the protein tyrosine phosphatase Shp2, which plays an important role in cell signaling, cell proliferation, differentiation and migration [15].The marketed anticancer drug Sunitinib [16] and Oratinib contains 2-oxoindolin-3-ylidene moiety where as Ilmofosin and Edelfosin contains phosphonate moiety and a recently marketed anticancer drug, Toceranib phosphate [17] contains 2-oxoindol-3-ylidene as well as phosphonates moiety. Considering the 3 biological importance of 2-oxoindolin-3-ylidene and α-aminophosphonates prompted us to synthesize coupled derivatives containing isatin based hydrazone and α-aminophosphonates with the hope to get novel hybrid derivatives.…”
Section: Introductionmentioning
confidence: 99%